2012
DOI: 10.1039/c2ob26460a
|View full text |Cite
|
Sign up to set email alerts
|

1,2,4-Dithiazole-5-ones and 5-thiones as efficient sulfurizing agents of phosphorus(iii) compounds – a kinetic comparative study

Abstract: The sulfurization efficiency of 25 3-substituted-1,2,4-dithiazole-5-ones and 5-thiones towards triphenyl phosphite in acetonitrile, DCM, THF and toluene at 25 °C was evaluated. All the 1,2,4-dithiazoles are much better sulfurizing reagents than commercially available agents (PADS, TETD, Beaucage's reagent). The most efficient sulfurizing agents in all solvents are 3-phenoxy (4), 3-phenylthio (5) and 3-ethoxy-1,2,4-dithiazole-5-one (1) whose reactivity is at least two orders of magnitude higher than that of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 68 publications
1
10
2
Order By: Relevance
“…From the data in Table , it is obvious that the second‐order rate constants show a significant dependence on solvent polarity which indicates development of substantial charges in the transition state. Such observations are completely different to what was observed in the case of structurally similar 1,2,4‐dithiazole‐5‐ones and 5‐thiones where the influence of solvent polarity on the rate of sulfurization was only negligible. From the data in Table , it is also possible to plot corresponding Hammett correlations (Fig.…”
Section: Resultscontrasting
confidence: 95%
See 4 more Smart Citations
“…From the data in Table , it is obvious that the second‐order rate constants show a significant dependence on solvent polarity which indicates development of substantial charges in the transition state. Such observations are completely different to what was observed in the case of structurally similar 1,2,4‐dithiazole‐5‐ones and 5‐thiones where the influence of solvent polarity on the rate of sulfurization was only negligible. From the data in Table , it is also possible to plot corresponding Hammett correlations (Fig.…”
Section: Resultscontrasting
confidence: 95%
“…Using 31 P NMR, we have found that the reaction of all 1,2,4‐dithiazolidines 1a , 1b , 1c , 1d , 1e , 1f , 1g with triphenylphosphines in CDCl 3 and CD 3 CN proceeds smoothly and the only products are the corresponding triphenylphosphinsulphides together with phenylisocyanates and carbonylsulfide which is consistent with previous results. Similar experiment with the least reactive triphenyl phosphite used in our previous study surprisingly showed that the parallel oxidation of trivalent phosphorus occurs and the product therefore contains a mixture of the desired triphenyl phosphorothioate (δ(CDCl 3 ) = 53.7 ppm) and triphenyl phosphate (δ(CDCl 3 ) = −17.3 ppm) in the ratios 1:3 – 1:5 depending on the water content (based on integration of peaks at 53.7 ppm and −17.3 ppm in 31 P NMR spectrum). This result could not be caused only by dissolved oxygen in deuterated solvent or by the presence of oxygen in the air above the sample in the NMR tube during measurement because the triphenyl phosphite itself does not undergo oxidation under these conditions.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations